Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
nguyễn nam dũng

Tính tổng : S = (-3)^0 + (-3)^1 + (-3)^2 +.......+(-3)^2015

BAN is VBN
21 tháng 5 2016 lúc 17:02

S = (-3)+ (-3)+ (-3)+ ... +  (-3)2015

=> 3S = (-3)+ (-3)+ (-3)+ ... +  (-3)2016

=> 3S + S = [(-3)+ (-3)+ ... +  (-3)2016] + [(-3)+ (-3)+ ... +  (-3)2015]

=> 4S = (-3)2016 + (-3)0

=> S = \(\frac{\left(-3\right)^{2016}+\left(-3\right)^0}{4}\)


Các câu hỏi tương tự
Ngọc Hà
Xem chi tiết
loan leo
Xem chi tiết
lutufine 159732486
Xem chi tiết
AFK
Xem chi tiết
đặng phương vi
Xem chi tiết
Trần Nhật Anh
Xem chi tiết
phan thuy trang
Xem chi tiết
Renian Karin
Xem chi tiết
Đỗ Thế Hưng
Xem chi tiết